+0  
 
0
970
1
avatar

What is the fourth term of a sequence with the recursive rule f(n)=-2f(n-1); f(1)=-3.5

Guest May 10, 2015

Best Answer 

 #1
avatar+26741 
+8

Each term beyond the first is -2 times the previous one, and there are n-1 terms beyond the first, so the n'th term is given by (-2)n-1 times the first term or:  f(n) = (-2)n-1*(-3.5)

 

The fourth term is then: f(4) = (-2)3*(-3.5)  = -8*(-3.5) = 28

.

Alan  May 10, 2015
 #1
avatar+26741 
+8
Best Answer

Each term beyond the first is -2 times the previous one, and there are n-1 terms beyond the first, so the n'th term is given by (-2)n-1 times the first term or:  f(n) = (-2)n-1*(-3.5)

 

The fourth term is then: f(4) = (-2)3*(-3.5)  = -8*(-3.5) = 28

.

Alan  May 10, 2015

8 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.